Dental age estimation by Demirjian's and Nolla's method: A comparative study among children attending a dental college in Lucknow (UP) - Shruti Sinha; Deepak Umapathy; Mathod C Shashikanth; Neeta Misra; Anshul Mehra; Ashish Kumar Singh (Wolters Kluwer Medknow Publications, 2014)
Introduction: Estimation of age is an important aspect of forensic science. The assessment of age is useful in forensic odontology and in treatments plans of orthodontic and pedodontic patients. Aims and Objectives: The aim of the study was to determine dental age from orthopantomograph using Demirjian's method and Nolla's method. It was also to evaluate the interrelationship between chronological and dental age according to both these methods and to evaluate which technique was better. Materials and Methods: The study was conducted in the Department of Oral Medicine and Radiology of Babu Banarasi Das College of Dental Sciences (UP, Northern India). A total of 300 subjects (150 girls and 150 boys) of age group from 6 years to 15 years were enrolled. These subjects were grouped by a difference of 1 year into 10 groups (each group comprised of 30 subjects: 15 males and 15 females). For every individual included in the study a panoramic radiograph was taken, with standard parameters and adequate protective measures. Results: The results imply that Demirjian's method is applicable to all age groups and for both genders with better accuracy than Nolla's method, which had a limited utility in younger age group. Thus Demirjian's method is a better method when compared to Nolla's method in Northern Indian population.